1995
DOI: 10.1002/ptr.2650090712
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycaemic activity of Nelumbo nucifera gaertn. (Fam. Nymphaeaceae) rhizome (methanolic extract) in streptozotocin‐induced diabetic rats

Abstract: The hypoglycaemic effect of the rhizome extract of Nelumbo nucifera was studied in streptomtwin-induced diabetic rats. A methanol extract of the plant obtained by soxhlet extraction from finely pulverized rhizomes was used. The LD9 of the extract was found to be 2 g/kg. The extract (300 mg/kg and 600 mg/kg, orally) caused a reduction of blood glucose levels in streptomtocin-induced diabetic rats by 53% (p Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 6 publications
0
18
0
Order By: Relevance
“…markedly reduced the blood sugar level of normal, glucose-fed hyperglycemic and streptozotocin-induced diabetic rats. The extract also found to improve glucose tolerance and potentiated the action of exogenously injected insulin in normal rats (Mukherjee et al, 1995(Mukherjee et al, , 1997.…”
Section: Nelumbo Nucifera Gaertn (Family: Nymphaeaceae)mentioning
confidence: 94%
“…markedly reduced the blood sugar level of normal, glucose-fed hyperglycemic and streptozotocin-induced diabetic rats. The extract also found to improve glucose tolerance and potentiated the action of exogenously injected insulin in normal rats (Mukherjee et al, 1995(Mukherjee et al, , 1997.…”
Section: Nelumbo Nucifera Gaertn (Family: Nymphaeaceae)mentioning
confidence: 94%
“…al., 1996b), antipyretic (Mukherjee et al, 1996c), antimicrobial (Mukherjee et al, 1995b,c;Mukherjee, 2002), hypoglycemic (Mukherjee et al, 1995d). Antioxidant activity of various parts of Nelumbo nucifera is well established, e.g.…”
Section: Introductionmentioning
confidence: 95%
“…Our previous studies have shown various pharmacological potential of the rhizome extract of Nelumbo nucifera, viz. hypoglycaemic, antidiarrhoeal, antimicrobial, diuretic, antipyretic, psychopharmacological, antiinflammatory activities (Mukherjee et al, 1995a(Mukherjee et al, ,b,c,d, 1996a(Mukherjee et al, ,b,c, 1997. Seed of the plant also proved to have several therapeutic potential including anti-ischemic (Kim et al, 2006), antioxidant , hepatoprotective (Sohn et al, 2003), antiproliferative (Liu et al, 2004), anti-inflammatory (Lin et al, 2006) activity.…”
Section: Introductionmentioning
confidence: 97%